Biophysical and functional study of CRL5Ozz, a muscle specific ubiquitin ligase complex - Yvan Campos (Scientific Reports, 2022)
Abstract Ozz, a member of the SOCS-box family of proteins, is the substrate-binding component of CRL5Ozz, a muscle-specific Cullin-RING ubiquitin ligase complex composed of Elongin B/C, Cullin 5 and Rbx1. CRL5Ozz targets for proteasomal degradation selected pools of substrates, including sarcolemma-associated β-catenin, sarcomeric MyHCemb and Alix/PDCD6IP, which all interact with the actin cytoskeleton. Ubiquitination and degradation of these substrates are required for the remodeling of the contractile sarcomeric apparatus. However, how CRL5Ozz assembles into an active E3 complex and interacts with its substrates remain unexplored. Here, we applied a baculovirus-based expression system to produce large quantities of two subcomplexes, Ozz–EloBC and Cul5–Rbx1. We show that these subcomplexes mixed in a 1:1 ratio reconstitutes a five-components CRL5Ozz monomer and dimer, but that the reconstituted complex interacts with its substrates only as monomer. The in vitro assembled CRL5Ozz complex maintains the capacity to polyubiquitinate each of its substrates, indicating that the protein production method used in these studies is well-suited to generate large amounts of a functional CRL5Ozz. Our findings highlight a mode of assembly of the CRL5Ozz that differs in presence or absence of its cognate substrates and grant further structural studies.